Surface passivation for ultrathin Al2O3 layers grown at low temperature by thermal atomic layer deposition. Issue 4 (28th November 2012) - Frascaroli, J.; Seguini, G.; Cianci, E.; Saynova, D.; van Roosmalen, J.; Perego, M.
Abstract Thin layers of Al2O3 with thickness tox ≤ 8 nm were grown by thermal atomic layer deposition at low temperature of 100 °C and applied to achieve functional surface passivation of crystalline silicon substrates. Measurements of the effective lifetime were performed to characterize the surface passivation effect. Lifetime values in the range of 0.5 ms were obtained for Al2O3 films with tox ≥ 6 nm upon post‐deposition annealing (PDA) at 250 °C in N2 atmosphere. However, when the thickness of the Al2O3 films was reduced to 4 nm, lifetime values well below 0.1 ms were observed even after PDA. Combined capacitance–voltage and conductance–voltage measurements were carried out to extract the amount of charges located near the silicon‐oxide interface and the density of electrically active interface states, respectively. The results of the electrical characterization were used to elucidate the intimate physical mechanisms that govern charge recombination at the Al2O3/Si interface. Density of interface states (a) and lifetime (b) values are reported as a function of the PDA temperature for Al2O3 films of three different thickness values: 4, 6, and 8 nm. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>